Influence Level Literacy the Financial to Control Cost and the Performance of the Financial on MSMEs on District Bojonegoro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine how much influence of financial literacy to the performance of the financial on the MSMEs and control cost in Bojonegoro District. Research this is research quantitative. Collection the data done by spreading question naires and then processed using the SPSS application. Total sample is 38 the sample actors MSMEs ssector culinary in sub-district bojonegoro. Results here are in fluence positive and significant Financial literacy variables on the cost control of reseresearch shows that. The influence positive and significant variable literacy Finance onthe performance ofthe financial SMEs. Tarch on the effect of financial literacy on MSMEs performance have very broad implications, both theoretically and practically. There is no significant effect of mediation between financial literacy variables on financial performance through cost control. The results of this study can enrich the Khazanah science, provide better policy recommendations, and help MSMEs in improving their financial performance. This study contributed a very valuable to the development of MSMEs in Bojonegoro.